2007
DOI: 10.1007/s00267-004-0355-8
|View full text |Cite
|
Sign up to set email alerts
|

Past On-Site Experience, Crowding Perceptions, and Use Displacement of Visitor Groups to a Peri-Urban National Park

Abstract: Past on-site experience was linked to the crowding perceptions and use displacement of 383 on-site visitors to the peri-urban Danube Floodplains National Park, Austria. Three visitor groups were determined according to their area experience: local residents from Vienna and rural communities, having the highest level of experience; regional visitors from the city and eastern Austria; and tourists from Austria and abroad with the lowest degree of experience. Crowding perceptions were significantly different acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 28 publications
4
56
0
1
Order By: Relevance
“…Another possibility is that perceptions of crowded parks may encourage physical activity participation for some users while discouraging use for physical activity for other users. Residents living near large open spaces or attractions are more likely to perceive crowding [80,81]. For example, a study in Central Europe found that more than 50 % of the local residents reported the park as crowded, while only 27 % of the regional visitors and 19 % of the tourists viewed it as crowded [80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that perceptions of crowded parks may encourage physical activity participation for some users while discouraging use for physical activity for other users. Residents living near large open spaces or attractions are more likely to perceive crowding [80,81]. For example, a study in Central Europe found that more than 50 % of the local residents reported the park as crowded, while only 27 % of the regional visitors and 19 % of the tourists viewed it as crowded [80].…”
Section: Discussionmentioning
confidence: 99%
“…Residents living near large open spaces or attractions are more likely to perceive crowding [80,81]. For example, a study in Central Europe found that more than 50 % of the local residents reported the park as crowded, while only 27 % of the regional visitors and 19 % of the tourists viewed it as crowded [80]. Some studies indicated that use of parks by friends and family, perceiving neighbors as being active, and having a friend to exercise with were related to more physical activity [32,38,79].…”
Section: Discussionmentioning
confidence: 99%
“…Of importance, 'number of people seen' was negatively significant for accepted crowding factor (maximum number of people to see) and the same result was observed for 'opportunity to escape crowd' ('number of people seen' and 'maximum number of people to see'). From the perspective of 'maximum number of people to see', it can be said that respondents fall under the crowding-averse category [10]. However, from respondents are interchange between crowding-averse and crowding-tolerant when analysed from the 'opportunity to escape crowd' and 'enjoyment level' point of views.…”
Section: Research Findingsmentioning
confidence: 99%
“…The paradigm shift between crowding-averse and crowding-tolerant, to a certain extent, is influenced by one's psychology stability in accepting changes of the surroundings. For instance, the difference in crowding standard between regional rural and urban visitors of a national park is fairly interlinks with the use displacement in addition to past experience and nous [10]. At a greater extent, the use displacement is also addressing the effect of surroundings (types and density) towards crowding standard of a site.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Urban sprawl is increasingly an issue in the planning and management of many cities and their hinterlands, with the latter including what have been variously termed peri-urban (Allen, 2003;Arnberger andBrandenburg, 2007), near-urban (DNRE, 1996) or urban fringe parks (Ramp et al, 2006). Australia has an unusually high incidence of protected areas abutting metropolitan areas and, with estimates of annual growth in visitation of 16% to 17%, compared to just 4% for remote protected areas (DRE, 1996), this preference for nature-based recreation and tourism close to home appears to be a growing one.…”
Section: Introduction Definitions Of Key Concepts and Overview Of Thmentioning
confidence: 99%